Analysis of the Effectiveness of the Independent Curriculum in Increasing Learning Independence: A Comparative Study Between High School and Basic Education Levels - Noho, Mubin; Adam, Adiyana; Usia, Rakiba; Yoioga, Tamsin; Bambang, Sumarni; Masuku, Mardia (Electronic Journal of Education, Social Economics and Technology, 2024)
This research analyzes the effectiveness of the Merdeka Curriculum in improving students' learning independence at high school and elementary school levels, with case studies at MAN 1 Ternate and MIN 1 Ternate. Using a qualitative approach, the research collected data through in-depth interviews, observations, documentation, and focus group discussions. The results showed significant differences in the level of learning independence between the two educational levels. High school students achieved an average learning independence score of 78.5%, while elementary students reached 62.7%. These differences were influenced by cognitive development factors, teacher readiness, and external support. High school students demonstrated better ability in planning learning, conducting independent learning, and evaluating learning outcomes. Meanwhile, elementary students required more intensive guidance but showed high enthusiasm in project-based learning. The research concludes that the implementation of the Merdeka Curriculum needs to be adapted to students' developmental characteristics at each educational level, emphasizing increased teacher readiness, especially at the elementary level, to maximize curriculum effectiveness in improving learning independence.